Nuclear Envelope Transmembrane Proteins in Myotonic Dystrophy Type 1 - Hintze, Stefan; Knaier, Lisa; Limmer, Sarah; Schoser, Benedikt; Meinke, Peter (Frontiers in Physiology, 2018)
Myotonic dystrophy type 1 (DM1) is a multisystemic disorder with predominant myotonia and muscular dystrophy which is caused by CTG-repeat expansions in the DMPK gene. These repeat expansions are transcribed and the resulting mRNA accumulates RNA-binding proteins involved in splicing, resulting in a general splicing defect. We observed nuclear envelope (NE) alterations in DM1 primary myoblasts. These included invaginations of the NE as well as an altered composition of the nuclear lamina. Specifically, we investigated NE transmembrane proteins (NETs) in DM1 primary myoblasts, staining to determine if their distribution was altered compared to controls and if this could contribute to these structural defects. We also tested the expression of these NETs in muscle and how localization changes in the DM1 primary myoblasts undergoing differentiation in vitro to myotubes. We found no changes in the localization of the tested NETs, but most tended to exhibit reduced expression with increasing DMPK-repeat length. Nonetheless, the DM1 patient expression range was within the expression range of the controls. Additionally, we found a down-regulation of the possible nesprin1 giant isoform in DM1 primary myoblasts which could contribute to the increased NE invaginations. Thus, nesprin1 may be an interesting target for further investigation in DM1 disease pathology.